Adsorption of Pb2+ ions in aqueous media using the new zeolite nanocomposite adsorbent CaOCdO/ZSM5 synthesized with new techniques - Meysam Sadeghi; Pourya Zarshenas (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2022)
ZSM-5 `is a porous zeolite material that reveals good activity for the adsorption of heavy metals and other contaminants for effluent purification. In this scientific research, we synthesized the novel CaO-CdO/ZSM-5 zeolite nanocomposite adsorbent and studied the effects of different parameters on the adsorption of Pb2+ ions from water media for the first time. About 99.2% adsorption removal efficiency was obtained after a contact time of 60 min and an adsorbent amount of 0.1g/L for an initial Pb2+ concentration of 200mg/L at pH 8 and temperature of 60oC. The adsorption kinetic fit well via the pseudo-second-order model. Furthermore, the adsorption results were reproduced using the Langmuir isotherm with a maximum adsorption capacity of mg/g. The thermodynamic data displayed that the adsorption of Pb2+ ions over the CaO-CdO/ZSM-5 nanocomposite was endothermic and spontaneous.